METHODOLOGICAL GUIDELINES OF SYNERGISTIC APPROACH IN ECONOMIC RESEARCH - N. Grazhevska (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article highlights the most important philosophical, ideological and theoretical-methodological gains of synergy in understanding of nature and development mechanisms of modern economic systems. Author analyzes present status and problems of application of synergetic approach in economic research.